IMPLEMENTASI PROFESIONALISME GURU DALAM MENINGKATKAN MUTU PEMBELAJARAN: STUDI KUALITATIF DI SMP MUHAMMADIYAH KOTA BONTANG - Ibrahim Robbaniy; Hardhina Rosmasita; Erna Yayuk (STKIP Subang, 2026)
The implementation of teacher professionalism is a key factor in improving the quality of learning in schools. This study employs a qualitative approach with a descriptive design to examine teachers’ professional practices in the context of learning at Muhammadiyah Junior High School in Bontang City. The research subjects consisted of the school principal and teachers selected through purposive sampling. Data collection was conducted through observation, interviews, and documentation, and was subsequently analyzed using an interactive model encompassing data reduction, data presentation, and drawing conclusions. The results indicate that teacher professionalism is reflected in systematic lesson planning, effective and varied instructional delivery, as well as continuous and reflective learning evaluation. Additionally, teachers demonstrated a commitment to competency development through training and professional collaboration. The implementation of teacher professionalism had a positive impact on the quality of learning, as evidenced by increased student engagement, improved quality of learning interactions, and enhanced student understanding of the material. Supporting factors included participatory school leadership, a conducive school culture, and the availability of facilities and infrastructure. Meanwhile, inhibiting factors include time constraints, administrative workload, and unequal access to professional development. These findings confirm that teacher professionalism contributes significantly to improving the quality of learning. Therefore, sustained efforts are needed through the strengthening of professional development, academic supervision, and the provision of adequate systemic support to optimize the quality of learning.